Conjunction Equivalent to Negation of Implication of Negative/Formulation 1/Reverse Implication

From ProofWiki
Jump to navigation Jump to search


$\neg \left({p \implies \neg q}\right) \vdash p \land q$


By the tableau method of natural deduction:

$\neg \left({p \implies \neg q}\right) \vdash p \land q$
Line Pool Formula Rule Depends upon Notes
1 1 $\neg \left({p \implies \neg q}\right)$ Premise (None)
2 2 $\neg \left({p \land q}\right)$ Assumption (None) Assume the negation of what is to be proved ...
3 2 $p \implies \neg q$ Sequent Introduction 2 Modus Ponendo Tollens
4 1, 2 $\bot$ Principle of Non-Contradiction: $\neg \EE$ 3, 1 ... and demonstrate a contradiction
5 1 $p \land q$ Reductio ad Absurdum 2 – 4 Assumption 2 has been discharged


Law of the Excluded Middle

This theorem depends on the Law of the Excluded Middle, by way of Reductio ad Absurdum.

This is one of the axioms of logic that was determined by Aristotle, and forms part of the backbone of classical (Aristotelian) logic.

However, the intuitionist school rejects the Law of the Excluded Middle as a valid logical axiom.

This in turn invalidates this theorem from an intuitionistic perspective.